Stress and sport performance: a PNEI multidisciplinary approach - Tossici, Giulia; Zurloni, Valentino; Nitri, Andrea (Frontiers in Psychology, 2024)
Stress control is essential for avoiding a state of anxiety in sport competitions, as this state may have negative effects on other psychological variables of athletes, decreasing their self-confidence and harming their attentional control. In the present contribution a distress intervention model developed from a PNEI perspective will be sketched out. Our theoretical-methodological proposal consists of the definition of an integrated protocol of psycho-biological assessment and intervention on the allostatic load and on the levels of distress/eustress detectable in the sport environment, in relation to the person's health/well-being condition and the impact of this condition on the quality of sport performance.This paradigm has the potential to explore both the psychological dimension of stress management and the psycho-educational and psycho-physical dimension, according to a truly integrated approach to the athlete's health and psychophysical well-being. Its multidisciplinary nature requires close cooperation between different professional figures, such as the mental coach, psychologist, nutritionist, osteopath, and physiotherapist, as well as biologists, physicians and kinesiologists, both in planning and in implementation and monitoring at all stages. The potential impact of the model on sport performance will be deeply discussed.Author Andrea Nitri is employed by Health Hub srl. The remaining authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.In the sports arena, athletes face numerous stressful situations, which are generated from different sources. In general, situations that are regarded as challenging, potentially threatening, or requiring a considerable waste of resources to deal with (coping strategies) are categorised as stressors. These may include environmental factors related to competitive performance, such as participation in major competitions, rivalry with an opponent, media attention, unsatisfactory refereeing, unfavourable weather conditions, or a decline in performance (Ntoumanis and Biddle 1998). Aspects related to the sports organisation of which the athlete is a part, such as economic insecurity, communication problems with the coach or teammates in team